Organizational Capacity of the Technical Implementation Unit in Implementing Revolving Fund Management Policy: Evidence from Riau Islands Province, Indonesia - Yasica Merulgia Yasica; Rudi Subiyakto; Okparizan Okparizan (CV. AFDIFAL MAJU BERKAH, 2026)
The revolving fund management policy is a strategic initiative of the Riau Islands Provincial Government aimed at improving access to capital for Micro, Small, and Medium Enterprises (MSMEs) and promoting regional economic development. However, the implementation of this policy has faced several challenges, including low loan repayment rates, invalid debtor data, weak monitoring systems, and limited coordination among implementing agencies. To address these issues, the Provincial Government established the Technical Implementation Unit (UPT) for Revolving Fund Management under the Regional Financial and Asset Management Agency (BKKAD) through Governor Regulation Number 12 of 2023.This study aims to analyze the organizational capacity of the UPT in implementing the revolving fund management policy in the Riau Islands Province. The research employs a qualitative descriptive approach using interviews, observations, and document analysis. The analysis is based on Thompson’s organizational capacity framework, which consists of technical, managerial, and institutional capacities. The findings reveal that the UPT has improved administrative coordination and governance mechanisms; however, its capacity remains constrained by limited human resources, inadequate information systems, weak managerial coordination, and insufficient institutional support. These challenges affect the effectiveness of revolving fund management and hinder efforts to optimize loan recovery and policy outcomes. Strengthening organizational capacity through human resource development, digital system enhancement, regulatory support, and stakeholder collaboration is essential for improving accountability and sustainability. The study concludes that although the establishment of the UPT represents a positive institutional reform, further capacity strengthening is required to ensure effective, transparent, and sustainable revolving fund management in the Riau Islands Province